Aerospace series. Specification for Bolts, Hexagonal head, Unified short threads below .250 inch, Alloy steel, Cadmium plated. Classification: Rm = 124 000 – 146 000 lbf/in2 (855 – 1 007 MPa) at ambient temp | +190 ºC. Specification. (24th October 2019) - British Standards Institution,
No abstract available